Hilirisasi Parfum Nilam dan Sereh Wangi Menuju Pembangunan Berkelanjutan - Aziza, Pretty Failasufa (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
Indonesia is one of the world's largest producers of essential oils, especially from patchouli (Pogostemon cablin) and citronella (Cymbopogon nardus). However, most of these commodities are still sold as raw materials with low added value. The absence of a strong downstreaming strategy has limited the sector's contribution to farmers' welfare and national industrial development. In fact, the potential to develop a local essential oil-based perfume industry is considerable, especially when integrated with sustainability principles and community empowerment. This study aims to examine the practices of essential oil perfume downstreaming in Indonesia in relation to the Sustainable Development Goals, while identifying supporting and inhibiting factors, as well as existing research gaps. The research method used is a Systematic Literature Review (SLR) of 21 peer-reviewed scientific articles selected through clear inclusion criteria. Thematic analysis was applied to synthesize major findings from each study. The review reveals that downstreaming success is influenced by technological innovation in extraction, consumer preference for natural and eco-friendly products, as well as the importance of authentication systems and digital marketing strategies. It also shows that Goals 12, 9, and 3 are the most frequently associated with the issue. This study concludes that essential oil perfume downstreaming has significant potential as a sustainable, inclusive, and community-based industrial strategy that can contribute meaningfully to sustainable development in Indonesia.